Credit Agreements With Banks - Lisna Wati Purba; Mella Ismelina Farma Rahayu (Edunity Kajian Ilmu Sosial dan Pendidikan, 2023)
Institution Banking is a financial institution that has strategic value in a country's economy. To achieve the specified goals, the company will use procedures that are most appropriate to the activities carried out by the company, especially in providing credit to its customers. In banking practice, we will know that there are sequences of activities or processes that occur starting from the credit applicant seeking information at the bank until the withdrawal of the loan can be realized. To obtain a clearer picture, these activities can be classified into three stages, namely: those interested in credit seeking information, obtaining information, and receiving forms (forms for submitting credit applications) from the bank, those interested in credit filling in and submitting forms to until the credit application is approved by the bank, the credit applicant applies for the realization of a credit withdrawal and the credit granting bank will realize it and to realize the credit a credit agreement is made first, where in banking the credit agreement can be made by notarial deed and private agreement